2019
DOI: 10.1016/j.jtho.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age on Outcomes with Immunotherapy in Patients with Non–Small Cell Lung Cancer

Abstract: Introduction: Immunotherapy has revolutionized the treatment of NSCLC, but little is known about the activity of programmed cell death 1 and programmed death ligand 1 blockade across age groups. Methods: We retrospectively evaluated patients with NSCLC who initiated programmed cell death 1 and programmed death ligand 1 inhibitors from January 2013 through July 2017. Medical records and radiographic imaging were reviewed to determine progression-free survival (PFS) and overall survival (OS). We also compared im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 14 publications
2
68
0
Order By: Relevance
“…Wu et al found older (≥65 years) patient derived better benefits than younger (<65 years) patients from the use of ICIs (10). However, patients more than 80 years old were reported to have shorter PFS compared with other age groups (11).…”
Section: Introductionmentioning
confidence: 96%
“…Wu et al found older (≥65 years) patient derived better benefits than younger (<65 years) patients from the use of ICIs (10). However, patients more than 80 years old were reported to have shorter PFS compared with other age groups (11).…”
Section: Introductionmentioning
confidence: 96%
“…Kugel et al found that responsiveness to anti-PD-1 was even enhanced in older human melanoma patients and aged mice, and this was associated with increased CD8 + T cell infiltration ( Kugel et al, 2018 ). Others have also found good ICB responsiveness in elderly patients with melanoma ( Ben-Betzalel et al, 2019 ; Betof et al, 2017 ) or non-small cell lung cancer ( Lichtenstein et al, 2019 ), and across multiple cancer types ( Corbaux et al, 2019 ). Overall, most human studies show at least similar efficacy of anti-CTLA-4 and anti-PD-(L)1 therapies in older compared to younger patients ( Huang et al, 2020 ; Pawelec, 2019 ; Poropatich et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Real-life data, such as our own retrospective analysis, may help to increase the knowledge of ICIs effectiveness in older patients with NSCLC. In different retrospective studies [14][15][16][17][18][19], older and younger patients had similar effectiveness, although the results in the 'oldest old' remain rather conflicting. Lichtenstein et al reported similar median PFS but significant lower median OS in patients 80 years or older (OS 3.6 months versus 12.9 months in patients age 70-79 years, 14.6 months in patients aged 60-69 years and 13 months in patients younger than 60 years; p = 0.011) [19].…”
Section: Discussionmentioning
confidence: 97%
“…In different retrospective studies [14][15][16][17][18][19], older and younger patients had similar effectiveness, although the results in the 'oldest old' remain rather conflicting. Lichtenstein et al reported similar median PFS but significant lower median OS in patients 80 years or older (OS 3.6 months versus 12.9 months in patients age 70-79 years, 14.6 months in patients aged 60-69 years and 13 months in patients younger than 60 years; p = 0.011) [19]. Multivariate Cox regression, adjusted for baseline characteristics such as ECOG-PS and comorbidity, demonstrated in this study that patients age 80 years or older had a significant higher hazard for death compared with younger patients (HR 2.74; p = 0.002) [19].…”
Section: Discussionmentioning
confidence: 97%